THE IMPACT OF POLITICAL TIES, FAMILY OWNERSHIP AND BOARD POSITIONS ON GOOD GOVERNANCE: A LITERATURE REVIEW - Agustina Wahyu Widyaningrum; Fajar Gustiawaty Dewi; Usep Syaipudin (Transpublika Publisher, 2024)
This article explores the evolution of corporate governance in Indonesia through literature review approach. The article accentuates the pivotal role of political connections in surmounting external challenges, while vigilantly recognizing potential risks, such as manipulated financial reporting aligned with the interests of controlling shareholders. Within the realm of family-owned enterprises, where familial influence often permeates key leadership roles, the centralized nature of family ownership introduces complexities in decision-making, necessitating a careful examination of policy quality to attain organizational objectives. In its conclusion, the study also underscores the perpetual necessity for transparent practices, stringent regulatory enforcement, and ethical governance. The intricate interplay between ownership structures, political affiliations, and corporate performance emerges as a crucial focal point for fostering enduring prosperity and resilience within the landscape of Indonesian businesses.